Fatigue Damage Monitoring of a Cast Iron Pipeline Using Distributed Optical Fibre Sensors. (2017) - Wong, L.; Rathnayaka, S.; Chiu, W.K.; Kodikara, J.
Abstract: Corrosion induced failures are common in cast iron (CI) pipes used in water supply networks. Over times, cracks may initiate from the corroded pits and grow when subjected to fatigue internal loading. When the particular region of the pipe loses its structural capacity, it will eventually lead to leakage or even pipe burst. Thus, it is important to use non-destructive techniques to perform permanent and real-time integrity monitoring on these pipelines. Distributed optical fibre sensors (DOFS) have been proposed to monitor the structural health of water pipelines for past decades. Most of the previous studies show that DOFS is effective in monitoring the condition of a pipeline and to assess the damage. This paper aims to experimentally demonstrate the ability of distributed optical fibre strain sensor to monitor the fatigue crack growth along the cast iron pipeline. The fatigue test was carried out using a large scale cyclic internal pressure loading facility. The distributed optical fibre sensor was instrumented on the pipe to monitor the condition of the pipe when subjected to internal pressure loading which vicinity to typical water pressure loading (operating pressure and pressure transient) experienced in the field. The measured response will show the potential application of distributed optical fibre sensor for crack detection, as well as monitoring the fatigue crack growth along the pipe. The results confirmed that DOFS is able to enhance the detection of cracks along the monitored pipe.